Pola penanganan korban perilaku perundungan (bullying) pada siswa SMPN Kecamatan Kediri Kabupaten Lombok Barat - Haslan, Muhammad Mabrur; Fauzan, Ahmad; Tripayana, I Nengah Agus (Jurnal Teori dan Praksis Pembelajaran IPS, 2021)
This study aims (1) to describe the pattern of handling victims of bullying in SMP Negeri Kediri District, West Lombok Regency (2) to identify obstacles in the handling of victims of bullying in SMP Negeri students in Kediri District, Regency. West Lombok. The method used in this research is a qualitative approach. The research location was carried out in SMPs throughout Kediri District, West Lombok Regency. Determination of informants using snowball sampling. Data collection methods are depth interviews), observation and documentation. The Research Result have been analyzed so that it is obtained: (1) conducting information selection (supporting network). (2) conducting the mentoring or peer monitoring stage. (3) make use of peer group or peer befriending. (4) conduct counseling and mediation. (5) conduct socialization and control, namely efforts to provide the understanding and continuous monitoring of victims of bullying.DOI: http://dx.doi.org/10.17977/um022v6i12021p33